Long Periodic Structure of a Room‐Temperature Ionic Liquid by High‐Pressure Small‐Angle X‐Ray Scattering and Wide‐Angle X‐Ray Scattering: 1‐Decyl‐3‐Methylimidazolium Chloride. Issue 12 (23rd April 2018) - Abe, Hiroshi; Hamaya, Nozomu; Koyama, Yoshihiro; Kishimura, Hiroaki; Takekiyo, Takahiro; Yoshimura, Yukihiro; Wakabayashi, Daisuke; Funamori, Nobumasa; Matsuishi, Kiyoto
Abstract: The Bragg reflections of 1‐decyl‐3‐methylimidazolium chloride ([C10 mim][Cl]), a room‐temperature ionic liquid, are observed in a lowly scattered wavevector ( q ) region using high‐pressure (HP) small‐angle X‐ray scattering methods. The HP crystal of [C10 mim][Cl] was characterized by an extremely long periodic structure. The peak position at the lowest q (1.4 nm −1 ) was different from that of the prepeak observed in the liquid state (2.3 nm −1 ). Simultaneously, Bragg reflections at high‐ q were detected using HP wide‐angle X‐ray scattering. The longest lattice constant was estimated to be 4.3 nm using structural analysis. The crystal structure of HP differed from that of the low‐temperature (LT) crystal and the LT liquid crystal. With increasing pressure, Bragg reflections in the high‐ q component became much broader, and were accompanied by phase transition, although those in the low‐ q component were observed to be relatively sharp. Abstract : Looking at the reflection : The Bragg reflections of 1‐decyl‐3‐methylimidazolium chloride ([C10 mim][Cl]), a room‐temperature ionic liquid, are observed in a lowly scattered wavevector ( q ) region using high‐pressure (HP) small‐angle X‐ray scattering methods. The crystal structure of HP differs from that of the low‐temperature (LT) crystal and the LT liquid crystal.